Remittances and Development : Lessons from Latin America - Fajnzylber, Pablo (Washington, DC: World Bank, 2012)
There are four main messages that emerge from this book. First, no matter how authors look at the issue, remittances are extremely important in the Latin American context. With remittances estimated to have topped more than US$50 billion in 2006, Latin America is now the main destination of these flows. Second, remittances generate a number of important positive contributions to economic development. In particular, they tend to reduce poverty and inequality in recipient countries, as well as increase aggregate investment and growth. Third, even though remittances have a positive impact on the development indicators of the recipient economies, the magnitude of the estimated changes tends to be modest. Fourth, policy makers may take actions to enhance the development impact of remittances. One important message of this book is that the way countries benefit from remittances appears to be positively related to the countries' own institutional and macroeconomic environments.